Gambaran Perilaku Etik Perawat Berdasarkan Penjabaran Kode Etik Keperawatan - Zainuddin, Suhenny; Saleh, Ariyanti; Kadar, Kusrini S (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Â Background. It is very important for nurses to carry out nursing care actions professionally by adhering to ethical principles. One way of ethical principles that must be adhered to by professional nurses is to refer to the elaboration of the code of ethics as a standard of service. Nursing codes of ethics are valid and useful decision-making tools for nurses in dealing with ethical problems in daily clinical practice. The aim of the literature study is to identify effective ethical behavior through the nursing code of ethics.Method: The data base used in making review literature is Pubmed, Google Scholar, wiley online library and Science Direct. there are 6 articles that meet the criteria.Â Results: Of the 6 articles used as a literature review, it was found that to support the ethical behavior of nurses according to the code of ethics in supporting nursing care for patients and collaboration between health teams, it was necessary to consider supporting factors and useful inhibiting factors to behave ethically. These factors are knowledge and perception and compliance with the application of ethics by nurses.Conclusion: nurses must have ethical competencies and skills to engage with the people they serve with sincerity, principled courage and compassion.Â